Maternal and Perinatal Outcome on Pregnancy with Covid-19 Infection at Dr. Wahidin Sudirohusodo Hospital Makassar During the Period of April-July 2020 - Fadlia Pratiwi Suyuthi1, Maisuri T. Chalid1, A. Nursanty Padjalangi1, Irawaty Djaharuddin2, Muh. Nas (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: The aims of this research is to notice maternal and perinatal outcomeon pregnant women withcovid-19 infection at Dr. Wahidin Sudirohusodo Hospital During the Period of April-July 2020.Method: This research is using descriptive method which is by taking data from the pregnant women withcovid-19 infection at Dr. Wahidin Sudirohusodo Hospital during the period of April 1st – July 12th 2020.The data covers the age, gestational age, amount of parity, symptoms, pregnancy complication, supportiveexamination results such asneutrofil score, limfosit, CT-scan Thorax, method of delivery, baby’s APGARscore, covid baby status, maternal death, perinatal death.Results: There are 26 pregnant patients characteristic subjects with covid-19 infection, mostly 20-35 yearsold, aterm gestational (>37 weeks), multiparity, low educational background, unemployed, mostly with nosymptoms, increasing limfositneutrofil ratio rate >3,13. Good maternal outcome, there are no maternal deathin this research. Perinatal outcome from 24 babies, 5 babies are confirmed covid-19 positive and all are ingood condition.Conclusion: This research concludes good maternal and perinatal outcome